The laws of niddah as a means of controlling female sexuality - Nadav Carmel, Hila (Humaniora. Czasopismo Internetowe, 2019)
This article presents how the laws of Niddah in Judaism are influenced by the cultural attitude to menstruation and how the cultural attitude to menstruation is related to the social status of women. The laws of Niddah are consider in historical and contemporary perspective with special interests in attitudes to women menstruation and sexuality. The social and biological domain are analyzed to understand the connections between power struggles and behavior regulations.